A retrospective analysis of the influencing factors of nucleic acid CT value fluctuation in COVID-19 patients infected with Omicron variant virus in Changchun city - Cao, Zhenghua; Sun, Feng; Ding, Huan; Tian, Zhiyu; Cui, Yingzi; Yang, Wei; Hu, Shaodan; Shi, Li (Frontiers in Public Health, 2024)
Objective This study aimed to determine the risk factors associated with fluctuations in nucleic acid CT values in patients infected with the Omicron variant during an outbreak at a hospital in Changchun city. Methods A retrospective analysis was conducted on general information, medical history, vaccination history, and laboratory test data of COVID-19 patients infected with the Omicron variant and admitted to the hospital in Changchun from March 2022 to April 2022. The study aimed to explore the factors influencing nucleic acid CT value fluctuations in COVID-19 patients infected with the Omicron variant in Changchun city. Results Fluctuations in nucleic acid CT values were significantly correlated with occupation composition (p = 0.030), hospital stay duration (p = 0.000), heart rate (p = 0.026), creatinine (p = 0.011), platelet count (p = 0.000), glutamic-pyruvic transaminase (p = 0.045), and glutamic oxaloacetic transaminase (p = 0.017). Binary logistic regression analysis revealed significant correlations between hospital stay duration (p = 0.000), platelet count (p = 0.019), heart rate (p = 0.036), and nucleic acid CT value fluctuations (p < 0.05), indicating that they were independent risk factors. Red blood cell count was identified as a factor influencing nucleic acid CT value fluctuations in Group A patients. Occupation composition, direct bilirubin, and platelet count were identified as factors influencing nucleic acid CT value fluctuations in Group B patients. Further binary logistic regression analysis indicated that occupational composition and direct bilirubin are significant independent factors for nucleic acid CT value fluctuations in Group B patients, positively correlated with occupational risk and negatively correlated with direct bilirubin. Conclusion Therefore, enhancing patients’ immunity, increasing physical exercise to improve myocardial oxygen consumption, reducing the length of hospital stays, and closely monitoring liver function at the onset of hospitalization to prevent liver function abnormalities are effective measures to control fluctuations in nucleic acid CT values.